Kingdom of the Netherlands-Netherlands : Selected Issues Paper. (IMF Staff Country Reports; Country Report ;, 2014)
This Selected Issues paper analyzes the housing prices, consumption, and the household debt overhang in the Netherlands. Deflated housing prices that were fueled by robust borrowing often leave in their wake households with heavy debt burden. This 'debt overhang' forces households into deleveraging-reducing their level of debt to sustainable levels. When deleveraging is brought about through reduced household consumption, it can contribute to a protracted 'balance sheet recession' as appears to be the case in the Netherlands. This paper estimates a simultaneous equations model of the Dutch economy using a three-stage least squares approach. Empirical results are supportive of the hypothesis that housing prices strongly affect private consumption.